1989
DOI: 10.1007/bf00156838
|View full text |Cite
|
Sign up to set email alerts
|

Fungal air-borne spores as health risk factors among workers in alimentary industries

Abstract: A survey to evaluate the occurrence of air-borne fungal spores in two different food industries, dairies and bakeries, was conducted. Our data revealed considerable fungal pollution in the environments of both industries, as well as some differences in the distribution of the genera of fungi recovered. Noteworthy was the frequent finding of numerous fungi frequently responsible for allergic rhinitis, asthma and other diseases, or well-known for their production of mycotoxins in foods or characterized by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…People working in catering are exposed to dust, fungi and viruses. Some studies carried out in food industries, such as bakeries or dairies, have shown a considerable fungal and organicdust pollution in their environments, which could imply a Using age-and period-speci®c rates for the whole cohort as standard b Adjusted for age, period and geographical category, taking other occupations in the general cohort as reference c For groups with at least two cases a continuous stimulation of the immune system (Palmas et al 1989;Godnic et al 1999;Amano et al 1998). In addition, propylene oxide used in the chemical and food industries has been related to dierent kinds of tumours, due to its strong cytotoxic and proliferative component, as has been shown in some experimental studies (Eldridge et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…People working in catering are exposed to dust, fungi and viruses. Some studies carried out in food industries, such as bakeries or dairies, have shown a considerable fungal and organicdust pollution in their environments, which could imply a Using age-and period-speci®c rates for the whole cohort as standard b Adjusted for age, period and geographical category, taking other occupations in the general cohort as reference c For groups with at least two cases a continuous stimulation of the immune system (Palmas et al 1989;Godnic et al 1999;Amano et al 1998). In addition, propylene oxide used in the chemical and food industries has been related to dierent kinds of tumours, due to its strong cytotoxic and proliferative component, as has been shown in some experimental studies (Eldridge et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there have been only anecdotal studies reporting the detection of Candida species in air [1,[12][13][14][15], and the concept of airborne candidiasis is not accepted. Yet, on the basis of our findings, it is tempting to speculate that during the special circumstances of the bomb explosion, the blast force could have at Florida International University on June 20, 2015 http://cid.oxfordjournals.org/ Downloaded from facilitated dispersal and transport of Candida in air, transforming it temporarily to an airborne pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Groups at risk of high exposure to this fungus and resultant hypersensitivity pneumonitis, include farmers; bird hobbyists; workers in sawmills, greenhouses, cane mills, or breweries; and people who work around mushrooms, tobacco, grain, compost piles, or decomposing haystacks. 44,45,46,47,48,49 Aspergillus versicolor has the potential to produce sterigmatocystin, a mycotoxin closely related in structure and biological activity to the aflatoxins. Although, aflatoxins are potent liver carcinogens and represent a risk to those exposed to high concentrations, there are no reported cases of liver cancer or other toxic effects associated with exposures to Aspergillus in office buildings.…”
Section: Aspergillusmentioning
confidence: 99%